Aortic Aneurysm 2017
DOI: 10.5772/65961
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Mediators in Abdominal Aortic Aneurysms

Abstract: Aortic wall dilatation in abdominal aortic aneurysms is characterized by extracellular matrix degradation together with a loss of smooth muscle cells from the aortic media. This occurs in conjunction with a marked inlammatory cell iniltration. The inlammatory cell is characteristic of the second phase of aneurysmal development-progression. It is widely accepted that usually there are three phases involved in the development of abdominal aortic aneurysms: initiation, progression and rupture. In this chapter, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…The finding that surgical treatment of AAA (OSR or EVAR) results in an improvement in FMD suggests the aneurysm itself to be a nidus of stimulus causing the deterioration of FMD observed during its natural history. We hypothesise that intraluminal thrombus is the source of such biological signals, as it is present in significant volumes in most AAAs and contains biologically active cells 25,26. This hypothesis requires further investigation.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The finding that surgical treatment of AAA (OSR or EVAR) results in an improvement in FMD suggests the aneurysm itself to be a nidus of stimulus causing the deterioration of FMD observed during its natural history. We hypothesise that intraluminal thrombus is the source of such biological signals, as it is present in significant volumes in most AAAs and contains biologically active cells 25,26. This hypothesis requires further investigation.…”
Section: Discussionmentioning
confidence: 93%
“…We hypothesise that intraluminal thrombus is the source of such biological signals, as it is present in significant volumes in most AAAs and contains biologically active cells. 25 , 26 This hypothesis requires further investigation.…”
Section: Discussionmentioning
confidence: 97%
“…14 There is mounting evidence of T-cells being active in AAA ILT and play a role in AAA pathophysiology. 15 Here we describe a novel role of Attractin in human AAA progression which warrants further mechanistic investigations.…”
Section: Discussionmentioning
confidence: 88%
“…The intraluminal thrombus (ILT) within abdominal aortic aneurysms has previously been held as a bystander to the disease (4). However, emerging evidence indicates ILT to be biologically active and contains inflammatory cells within a network of canaliculi (5)(6)(7). In addition to low ILT volume as a feature of likely persistent endoleak (adopted by the Massoni et al), it has also been observed the spatial distribution of ILT predicts the likelihood of T2E after EVAR.…”
mentioning
confidence: 99%